Pengaruh Work-life Balance dan Stres Kerja terhadap Turnover Intention Karyawan Gen Z di Wilayah Kabupaten Bekasi - Rizky Septianini (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to determine the effect of work-life balance and work stress on turnover of Gen Z employees in the Bekasi Regency area. This research was conducted on Gen Z employees who live in Bekasi Regency with a sample of 60 respondents. This research is quantitative research. The data in this research was obtained using a questionnaire with Likert scale measurements using the purposive sampling method. Hypothesis testing uses IBM SPSS Windows version 29 software. The data analysis methods used are data quality testing, classical assumption testing, hypothesis testing and coefficient of determination analysis. Based on the results of the t test, it shows that work-life balance has a negative and significant effect on turnover with a value of -2.951 < 2.002 and a sign value of 0.005 < 0.05. Work stress has a positive and significant effect on turnover with a value of 2.324 > 2.002 and a sign value of 0.024 < 0.05. Based on the F test, work-life balance and work stress together have a significant influence on Gen Z employee turnover in the Bekasi Regency area with a value of 5,530 > 4.01 and a sig value of 0.006 < 0.05.